Administration of an LXR agonist promotes atherosclerotic lesion remodelling in murine inflammatory arthritis. Issue 4 (18th April 2023) - Dragoljevic, Dragana; Lee, Man Kit Sam; Pernes, Gerard; Morgan, Pooranee K; Louis, Cynthia; Shihata, Waled; Huynh, Kevin; Kochetkova, Arina A; Bell, Patrick W; Mellett, Natalie A; Meikle, Peter J; Lancaster, Graeme I; et al.
Abstract: Objectives: The leading cause of mortality in patients with rheumatoid arthritis is atherosclerotic cardiovascular disease (CVD). We have shown that murine arthritis impairs atherosclerotic lesion regression, because of cellular cholesterol efflux defects in haematopoietic stem and progenitor cells (HSPCs), causing monocytosis and impaired atherosclerotic regression. Therefore, we hypothesised that improving cholesterol efflux using a Liver X Receptor (LXR) agonist would improve cholesterol efflux and improve atherosclerotic lesion regression in arthritis. Methods: Ldlr −/− mice were fed a western‐type diet for 14 weeks to initiate atherogenesis, then switched to a chow diet to induce lesion regression and divided into three groups; (1) control, (2) K/BxN serum transfer inflammatory arthritis (K/BxN) or (3) K/BxN arthritis and LXR agonist T0901317 daily for 2 weeks. Results: LXR activation during murine inflammatory arthritis completely restored atherosclerotic lesion regression in arthritic mice, evidenced by reduced lesion size, macrophage abundance and lipid content. Mechanistically, serum from arthritic mice promoted foam cell formation, demonstrated by increased cellular lipid accumulation in macrophages and paralleled by a reduction in mRNA of the cholesterol efflux transporters Abca1, Abcg1 and Apoe . T0901317 reduced lipid loading and increased Abca1 and Abcg1 expression in macrophages exposed to arthritic serum and increased ABCA1 levels in atherosclerotic lesions of arthritic mice. Moreover, arthritic clinical score was also attenuated with T0901317. Conclusion: Taken together, we show that the LXR agonist T0901317 rescues impaired atherosclerotic lesion regression in murine arthritis because of enhanced cholesterol efflux transporter expression and reduced foam cell development in atherosclerotic lesions. Abstract : In this study, we revealed that administration of a liver X Receptor (LXR) agonist (T0901317) to atherosclerotic‐prone mice with inflammatory arthritis reduces atherosclerosis and systemic cytokines along with joint inflammation. We have previously shown that arthritic mice have enhanced myelopoiesis because of defective cholesterol metabolism in haematopoietic stem and progenitor cells (HSPCs). However, LXR activation was unable to restore the expression of its target cholesterol efflux genes Abca1, Abcg1 or Apoe in HSPCs and had no impact on myelopoiesis. Instead, we observed an increase in ABCA1 expression in plaque macrophages and reduced foam cell formation along with lower levels of plaque tumor necrosis factor levels.